601 Increased institutional surgical experience in robot-assisted radical hysterectomy for early stage cervical cancer reduces recurrence rate. results from a nationwide study. (14th December 2020) - Ekdahl, Linnea; Wallin, Emelie; Alfonzo, Emilia; Reynisson, Petur; Lönnerfors, Celine; Dahm-Kähler, Pernilla; Falconer, Henrik; Persson, Jan
Abstract : Introduction/Background: The aim of this study was to evaluate the impact of institutional surgical experience on recurrence following robotic radical hysterectomy (RRH) for early stage cervical cancer. Methodology: All women in Sweden who underwent an RRH for stage IA2-IB1 cervical cancer at tertiary referral centers from its implementation in December 2005 until June 2017 were identified using a Swedish nationwide register and local hospital registers. Registry data was controlled by a chart review on all women. Recurrence rates and pattern of recurrence was compared between early and late (≤50 vs >50 procedures) institutional series. Results: 635 women were included. Regression analysis identified a lower risk of recurrence with increased experience but without a clear cut off level. Among the 489 women who did not receive adjuvant radio chemotherapy (RC-T), the rate of recurrence was 3.6% in the experienced cohort (>50 procedures) compared to 9.3% in the introductory cohort (p<0.05). This was also seen in tumors <2 cm regardless of RC-T (p<0.05) whereas no difference in recurrence was seen when analyzing all women receiving RC-T. Conclusion: In conclusion, the rate of recurrence following RRH for early stage cervical cancer decreased with increased institutional surgical experience, in tumors <2 cm and in women who did not receive adjuvant RC-T. Disclosures: Jan Persson, Henrik Falconer and Celine Lönnerfors have received honoraria for lectures and proctoring in robotic surgery, all outside the presented research. The other authors have no conflicts of interest.